"Evidence for a robust, estradiol-associated sex difference in narrative-writing fluency": Correction - Schultheiss, Oliver; Köllner, Martin; Busch, Holger; Hofer, Jan (Neuropsychology, 2021)
Reports an error in "Evidence for a robust, estradiol-associated sex difference in narrative-writing fluency" by Oliver C. Schultheiss, Martin G. Köllner, Holger Busch and Jan Hofer (Neuropsychology, 2021[Mar], Vol 35[3], 323-333). In the original article, there was an error in Table 1. The df for "18-50 years (adult men and premenopausal women)," originally read "1, 17," but should have read "1, 71." The online version of this article has been corrected. (The following abstract of the original article appeared in record 2020-71595-001). Objective: Despite evidence for an estradiol-linked sex difference in verbal fluency favoring women, recent reviews question this difference. We therefore examined the issue based on a narrative task that we have administered to different populations for over 20 years. Method: We meta-analyzed 98 studies (N = 11,528) conducted by our laboratories and that featured measures of biological sex and storytelling. We ran primary-data analyses (N = 797) on an overlapping subset of these studies that also included salivary hormone and digit ratio measures. Results: Women told longer stories than men, d = 0.31, 95% CI [0.24, 0.38], an effect that did not vary by geographic region but was moderated by cue type (verbal: d = 0.57, [0.44, 0.71]; pictures: d = 0.29, [0.22, 0.36]), response modality (oral: d = -0.04, [-0.18, 0.09]; handwriting: d = 0.39, [0.31, 0.47]; typing: d = 0.31, [0.21, 0.42]), and age (prepubertal children: d = 0.13, [-0.04, 0.30]; pubescents: d = 0.48, [0.23, 0.74]; premenopausal adults: d = 0.36, [0.29, 0.42]; postmenopausal adults: d = -0.09, [-0.35, 0.16]). Consistent with the age effect, estradiol, a sex-dimorphic hormone during the reproductive life stage, was a specific mediator of the sex difference in narrative-writing fluency. This mediation effect was moderated by prenatal hormone exposure, estimated via digit ratio. Conclusions: When verbal fluency is assessed through narrative writing, a robust female advantage becomes evident. It is associated with the reproductive life stage and variations in current estradiol concentrations, particularly in individuals prenatally exposed to relatively more estradiol than testosterone. (PsycInfo Database Record (c) 2021 APA, all rights reserved).
CRIS-Team Scopus Importer:2024-12-16